Analisa dan Perancangan Sistem Informasi Sekolah SMK Bina Putra Mandiri Berbasis Website Menggunakan Framework Laravel - M. Adi Siswanto; Bashar Awaluddin Nafsah; Heri Susanto; Salwa Juani Adrasah; Aries Saifudin (Shofanah Media Berkah, 2023)
This research addresses the issues faced by SMK Bina Putra Mandiri school in terms of efficiency and effectiveness in administrative processes. The identified problems include the time-consuming nature of managing student and staff data, lack of integration between different departments, and difficulties in delivering timely and accurate information to stakeholders. To address these issues, this study proposes the design and implementation of a web-based school information system using the Laravel framework. The methodology employed involves needs analysis through data collection via interviews and observations. Based on the analysis, an integrated school information system is designed using the popular Laravel framework for web application development. In the application of this methodology, features provided by the Laravel framework, such as user management, student and staff data management, and information delivery through easily accessible web pages, are implemented. The proposed information system is expected to enhance efficiency and accuracy in school administration. The results of testing and evaluation demonstrate that the implementation of the web-based school information system using the Laravel framework effectively addresses the identified issues. It significantly reduces the time required for managing student and staff data, improves integration between different departments, and facilitates the timely and accurate delivery of information to stakeholders. Thus, the application of this methodology offers significant benefits in enhancing the efficiency and effectiveness of school administrative processes at SMK Bina Putra Mandiri.